Direct Numerical Simulation of Three-dimensional Gravity Current on a Uniform Slope. (2015) - Ooi, A.; Zgheib, N.; Balachandar, S.
Abstract: Gravity currents occur when fluids of different density are brought together. When gravity currents travel down a uniform slope, buoyancy effects become more important and changes the physical dynamics of its motion. In the present paper, we report data from full three-dimensional direct numerical simulation of gravity currents propagating down a uniform slope. Our data shows that in most cases, the gravity current evolve to a shape that is similar to a triangular wedge. The physical mechanisms leading to formation of this triangular shape and the dynamics of such a structure is presented